Estimation of paddlefish (Polyodon spathula Walbaum, 1792) spawning habitat availability with consumer‐grade sonar. (1st December 2017) - Schooley, J. D.; Neely, B. C.
Summary: The paddlefish ( Polyodon spathula Walbaum, 1792) is a springtime migrant that requires discrete abiotic conditions such as water temperature, discharge, and substrate composition for successful spawning and recruitment. Although population declines have prevailed throughout much of the species range, Oklahoma paddlefish are abundant and support popular recreational snag fisheries – most notably in Grand Lake. This stock utilizes the Grand Lake's two primary headwaters, the Neosho and Spring rivers, with only episodic recruitment success. However, relationships between suitable spawning habitat and water level have not been evaluated in this system. Using consumer‐grade sonar equipment, this study identified and quantified hard river substrates (such as cobble and bedrock) and investigated proportional habitat availability at a variety of simulated river conditions. Sonar data were used to construct 49‐m 2 grids of depth and bottom hardness ( H ) ranging from 0.0 (soft) ‐ 0.5 (hard). Ground‐truthing samples of bottom composition were collected with a grab sampler and by visual identification. Substrate types were pooled into two categories: soft substrates ( H  <   0.386) and spawning substrates ( H  ≥   0.386) allowing for estimation of available spawning habitat in each river. Spawning habitat comprised 69% of total available habitat for the Neosho River (6.5 ha/km) and 58% for the Spring River (7.9 ha/km). Estimated spawning habitat was simulated over a range of river stages and predictive models were developed to estimate proportional spawning habitat availability (PHA). Although the Spring River contains more concentrated spawning habitat in closer proximity to Grand Lake, the Neosho River contains a greater quantity over nearly twice the distance to the first migration barrier, has a larger watershed, and demonstrates greater PHA at lower river stages. Model results were validated in context of known high and low recruitment years, where a greater frequency and duration of days with ≥90% PHA were observed in good recruitment years, particularly in the Neosho River. In total, results suggest the Neosho River has greater value for paddlefish reproduction than the Spring River. Research‐informed harvest management will remain critical to the conservation of wild‐recruiting stocks for continued recreational use in Oklahoma.